(3GdHQb GdjeGfi aj GdaJM GdYKeGfi (B( (3aJM Gdjef (B)s - (3eMeO Hf CMeO Hf eMeO Hf bGVj NGf eMehO GdfgQhGdj GdMfaj Gdecj , bWH GdOjf,J (B988 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fUQ GdOjf GdMfjai HUGQe hSfGf s
(3BNQgG (B:s
(3gPG BNQ GdcJGH HYhf Gdedc GdhgGH s
(3fSNI KGdKIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B17s
Keywords: (3GdJGQjNs